Síndrome de Waardenburg: relato de um caso clínico - FERREIRA, Juliano Rocha (2022)
Syndrome of Waardenburg is a hereditary disease of dominant autosomic inheritance, in the majority of the cases with variable expressivity and penetrance, that if characterizes for congenital, deafness, dystopia canthorum, alterations to pigment of the iris and the hair. It is caused by located genetic mutations in chromosomes 2 and 3. The findings most important are: alterations in the pigmentation of the skin and annexes, and neurosensorial congenital deafness that finishes for bringing alterations in the linguistic development of the carrier. In the social context, its importance is on the insertion of the individual as a whole, over all when sensorial problems are gifts. The diagnosis of the illness is made through the comment of the classic phenotypes signals of the illness, beyond audiologic evaluation, analysis of the desoxirribonucleic acid (DNA), beyond histopathologic analysis of the hypochromics injuries and the internal ear. One is about an individual, observational study, predominantly descriptive, type case report, that objectified to tell a carrier of Syndrome of Waardenburg taken care of in a university hospital. The attendance was carried through the ambulatory level, through serial outpatient visit. One identified prematurely gray of hair, hypoisocromic bilateral iris, absence of dystopia canthorum, neurosensorial congenital bilateral deafness, alterations to pigment in left foot, hypoplasia nasal and dysplasia alterations in average face; index W was of 1,4951. The emotional alterations had demonstrated to behavior for times aggressive with caregiver, fact aggravated for the auditory deficiency of the patient.